Protection of Ecosystems and Philosophy of Organism: Reflections for a new Environemntal Law Aesthetics (Nóema, 2020)
Process and Reality’s value is not limited in general ecologically and legally considerations. After almost a century, Alfred Whitehead’s work suggests a change in perspective with definitely practical implications. The purpose of this contribution consists in highlighting, through Whitehead’s Philosophy of Organism, the oxymoronic nature of contemorary environmental law. A possible solution to the problems in the protection of ecosystems is proposed too.
Keywords: Philosophy of organism; Environemntal law; Ecology; Ecosystem; Multi Criteria Decision Making; Aesthetics